IMPLEMENTASI TEKNIK PENGEDITAN DALAM PRODUKSI WEB SERIES COMPANY PROFILE UNTUK MENCIPTAKAN EFEK VISUAL YANG IMERSIF - Garry Leroy Secunda Neville Siahaan; Priatna, Wahyu Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study implements immersive editing techniques using the VividPulse approach in the production of a web series company profile for Halaman Omah (Halom Coffee). The research focuses on synchronizing visual rhythm and atmospheric audio to translate the cafe's physical atmosphere into an authentic digital representation. Findings demonstrate that post-production techniques—including emotion-based footage selection, precise sound design, and consistent color grading—successfully create an immersive sensory experience for social media audiences. This project proves that meticulous visual packaging in a dynamic vertical format effectively enhances the partner's brand identity and digital marketing appeal.